2021
DOI: 10.3390/su13041979
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainability: Impact Factors on Organizational Innovation in the Industrial Area

Abstract: In recent years, the principle of sustainability has received increasing attention in corporate governance, and corporate sustainability is usually achieved through organizational innovation. The purpose of this study is to identify the factors that are critical for companies to influence organizational innovation when promoting Industry 4.0. Our research analyzes the relationship between these factors and Industry 4.0, human resources, and corporate sustainability to investigate organizational innovation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 90 publications
0
12
0
4
Order By: Relevance
“…Similarly, Zang et al ( 2021 ) found that understanding the role of customers in business increases the sustainability and performance of SMEs for long-time revenues. Fan et al ( 2021 ) focused on promoting Industry 4.0 and stated that the most crucial innovation that affects organisational sustainability is influenced by customer orientation. Therefore, based on the findings of prior studies, this study proposed the following hypotheses:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Similarly, Zang et al ( 2021 ) found that understanding the role of customers in business increases the sustainability and performance of SMEs for long-time revenues. Fan et al ( 2021 ) focused on promoting Industry 4.0 and stated that the most crucial innovation that affects organisational sustainability is influenced by customer orientation. Therefore, based on the findings of prior studies, this study proposed the following hypotheses:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to the configuration results of innovation performance, knowledge sharing plays a core role in multiple configurations. This indicates that no matter whether there is a good open innovation environment or not (Fan et al, 2021)…”
Section: Research Implicationmentioning
confidence: 99%
“…El crecimiento de la sostenibilidad organizacional se verá en riesgo si los gobernantes o líderes industriales, emprenden iniciativas de innovación y desarrollo limitadas a crear conocimiento útil que conduzca a crecer únicamente en aspectos de rentabilidad, y no en una transformación verdadera para innovar y generar valor a todas las partes que integran su entorno más cercano (Fan et al, 2021). Para ampliar las problemáticas generadas a partir de no ir más allá de los beneficios monetarios en los procesos de cambio organizacional, es importante plantear que al implementarse políticas de RSE no se observan cambios significativos en el corto plazo en el desempeño empresarial, pero indicadores de transparencia y reputación tuvieron cambios positivos inmediatos, lo que demuestra las propiedades a largo plazo en cuanto a beneficios corporativos de las estrategias sostenibles (Chen et al, 2020).…”
Section: Perspectiva 2: Tendencias Del Gobierno Corporativounclassified